Wings of fire. The graphic novel. Book three, The hidden kingdom - Deutsch, Barry; Swirsky, Rachel; Holmes, Mike (New York : Graphix, 2019)
Tsunami, heir to the SeaWing throne, is returning home for the first time since she was stolen as an egg, her mother, Queen Coral, welcomes her, but a mysterious assassin has been killing off her heirs for years.
Based on: The lost heir by Tui T. Sutherland.
2.9
3-6
GN730L
Keywords: Dragons -- Comic books, strips, etc. -- Fiction; Prophecies -- Comic books, strips, etc. -- Fiction; Fantasy comic books, strips, etc; Dragons -- Juvenile fiction; Prophecies -- Juvenile fiction; Fantasy; Graphic novels; Fantasy comics; Graphic novel adaptations; Graphic novels; Comics (Graphic works)